Effects of Na and K co-doping on growth and scintillation properties of Eu:SrI2 crystals. (July 2016) - Ito, Tomoki; Yokota, Yuui; Kurosawa, Shunsuke; Kral, Robert; Pejchal, Jan; Ohashi, Yuji; Kamada, Kei; Nikl, Martin; Yoshikawa, Akira
Abstract: We grew Na and K co-doped Eu:SrI2 [Na, Eu:SrI2 and K, Eu:SrI2 ] crystals by a modified micro-pulling-down method to reveal the co-doping effects on the crystal growth and scintillation properties. The non-codoped, Na0.5%, Na1.0%, K0.5% and K1.0%, Eu:SrI2 crystals indicated high transparency while the milky parts were generated in the Na5.0% and K5.0%, Eu:SrI2 crystals. The light yields of Na, Eu:SrI2 and K, Eu:SrI2 crystals under γ-ray irradiation were decreased by the Na and K co-doping. On the other hand, there was a small change within 940–1020 ns in the decay times by the Na and K co-doping. In the light yield proportionality under γ-ray irradiation, the non-proportionality in the low energy region was improved by Na and K co-doping. Highlights: Na or K co-doped Eu:SrI2 crystals were grown by the modified μ-PD method. The milky parts were generated in the Na5.0% and K5.0%, Eu:SrI2 crystals. The light yield of Eu:SrI2 was decreased by the Na or K co-doping. The decay times of Eu:SrI2 were almost constant by the Na or K co-doping. The non-proportionalitywas improved in the low energy region by the K co-doping.